Topographic and Geodetic Supply Applied Devices and State Real Estate Cadastre - Tojidinova F.M (International Journal on Orange Technologies, 2022)
This article examines the generalization and analysis of information materials on the areas of application, principles of construction and operation of air laser systems used for topographic and geodetic support for maintaining the state cadastre of real estate. An analysis was made of the principles of construction, operation and main characteristics of air laser systems, their main advantages and disadvantages.